Implementasi Bimbingan dan Konseling Daring pada Madrasah Tsanawiyah di Jawa Timur - Agus Akhmadi; Ninik Supriyati (Andragogi: Jurnal Diklat Teknis Pendidikan dan Keagamaan, 2021)
[IMPLEMENTATION OF ONLINE GUIDANCE AND COUNSELING AT MADRASAH TSANAWIYAH IN EAST JAVA] Online guidance and counseling service is a service that is used during the pandemic. This study aims to describe the process and results of online counseling services in madrasas. The research method used is a survey with a descriptive approach. Research respondents were 383 students who received online guidance and counseling services at Madrasah Tsanawiyah. Questionnaires and interviews were used to collect the data. The instrument is uploaded in a google form, sent to the students through the guidance and counseling teachers. The questionnaire data were processed by descriptive statistics and analyzed through descriptive qualitative techniques. The results of this study indicate that online guidance and counseling services are carried out well. The online service process is fun and easy for students, the service is effective. There was an obstacle for several students due to the internet problem.